2020
DOI: 10.1186/s13017-020-00338-9
|View full text |Cite
|
Sign up to set email alerts
|

Management of liver trauma in urban university hospitals in India: an observational multicentre cohort study

Abstract: Background Low- and middle-income countries (LMICs) contribute to 90% of injuries occurring in the world. The liver is one of the commonest organs injured in abdominal trauma. This study aims to highlight the demographic and management profile of liver injury patients, presenting to four urban Indian university hospitals in India. Methods This is a retrospective registry-based study. Data of patients with liver injury either isolated or concomitant with other injuries was used using the ICD-10 code S36.1 for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Significantly, even at higher liver injury grades such as 3, 4, and 5, these patients were nonoperatively managed, and none died. These results were similar to those of Sinha et al, with 71.2% of their patients undergoing NOM at a success rate of 90% [23]. Moreover, a prospective Saudi study by Ghnnam et al [24] that evaluated liver trauma patients over four years revealed that conservative management had a success rate of 100%.…”
Section: Discussionsupporting
confidence: 84%
“…Significantly, even at higher liver injury grades such as 3, 4, and 5, these patients were nonoperatively managed, and none died. These results were similar to those of Sinha et al, with 71.2% of their patients undergoing NOM at a success rate of 90% [23]. Moreover, a prospective Saudi study by Ghnnam et al [24] that evaluated liver trauma patients over four years revealed that conservative management had a success rate of 100%.…”
Section: Discussionsupporting
confidence: 84%
“…However, laparoscopy as an initial approach for liver trauma is not recommended. Currently, the majority of patients with blunt liver trauma, especially children, were treated with a nonoperative management strategy, while those with hemodynamic instability and nonresponsiveness should undergo an operation (8,9). Other indications for an operation were some complications associated with nonoperative management strategies, such as hemorrhage, bile peritonitis, abdominal compartment syndrome, and liver compression (10).…”
Section: Discussionmentioning
confidence: 99%
“… 7 Depending on the velocity of injury the severity might be diverse, ranging from simple abdominal abrasions to life-threatening organ injury which needs prompt intervention and even with best efforts might even result in death. 8 …”
Section: Discussionmentioning
confidence: 99%